The Relationships Between Daily Sleepiness and Cardiovascular Health Indicators in the Older Adults - Asghar Shahbazi; Leila Miri; Mahshid Foroughan; Mohsen Vahedi (University of Social Welfare & Rehabilitation Sciences, 2021)
Objectives: Cardiovascilar disesases and sleep disorders are two major health problems common in old age. The aim of the present study was to examine the relationship between daytime sleepiness and cardiovascular indices among Iranian older adults. Methods & Materials: A cross-sectional design was used. The sample included 321 older adults who were selected from primary healthcare centers in Kiar County, Chaharmahal and Bakhtiari Province, Iran, using Non-random sampling available method. The data was gathered after taking informed concent, using a demographic questionnaire, Epworth Sleepiness Scale, anthropometric measurements, and relevant paraclinical tests. Chi-squared test, Mann-Whitney U test, Kruskal Wallis test, and Spearman's correlation coefficient were used to analyze the data. All the analyses were performed using SPSS, version 23. Results: The data showed 23.67%, 19%, and 7% of the participants had mild to moderate and severe daytime sleepiness, respectively. There was a significant association between daytime sleepiness and age (r=0.121, P=0.03). Moreover, significant positive correlations were found between daytime sleepiness and BMI (r=0.170, P=0.002), systolic blood pressure (r=0.235, P<0.001), diastolic blood pressure (r=0.216, P<0.001), abdominal obesity (r=0.293, P<0.001), and neck circumference (r=0.239, P<0.001). Conclusion: Given the positive relationships between daytime sleepiness and some cardiovascular health indices, daytime sleepiness assessment in primary healthcare services for the elderly, especially for those with a history of cardiovascular events, is suggested. More research to illustrate the cause and effect between these two is warranted.